O horrível, o devir e as quadrinistas: análise estética de graphic novels de horror feitas por mulheres - MATTOSINHO, ALICE G (2020)
With the legitimization of graphic novels and the increasing volume of independent comics being published, female comic book artists and writers, although being in smaller numbers when compared to male workers, have had great success in horror comics publishing, being awarded with significant awards during the latest years. This dissertation’s goal is to aesthetically analyze five horror graphic novels published after 1992, made by women, whose work achieved critically acclaimed success, printed for north american, french-belgium and japanese industries. The propositions from McCloud, Hatfield, Groensteen, Deleuze, Guattari, Kristeva,Derrida, Carrol, among others, were used when looking for similarities and disparities between those graphic novels that may enlighten women’s horror comics’ potence, observing a tendency on using the becoming in all the novels.